X-Ray Cephalometric Analysis of the Effects of Angle Class II and III Malocclusion on the Upper Airway Width and Hyoid Position between Parents and Children of Uygur Nationality. (19th July 2022) - Cheng, Lijun; Jiang, Yuxin; Man, Shasha; Wang, Yanan; Yang, Yan; Zhou, Mi
Abstract : Objective . The objective of this paper is to analyze the effect of angle class II and III malocclusion on the sagittal diameter of the upper airway between parents and children of Uygur nationality and to compare the degree of influence. Methods . 29 Uygur adolescents with malocclusion and their fathers (mothers) were selected as our subjects via X-ray cephalometric radiograph to analyze the difference between the upper airway sagittal dimension and normal occlusion and compare the influence of malocclusion on the upper airway between parents and children. Results . Compared with normal group, the vertical distance from the hyoid point to orbital-ear plane (H-FH) and vertical distance from hyoid point to the mandibular plane (H-MP) in angle class II malocclusion elevated signally, while the vertical distance from hyoid point to anterior cervical plane (H-VL), PNS-UPW, H-FH, and H-MP decreased significantly; compared with normal group: the distance between the posterior nasal spine and the upper pharynx wall (PNS-UPW), H-FH, and H-MP in angle class III malocclusion visually reduced, while PAS, and horizontal distance from the hyoid point and center point of sella turcica to orbital-ear foot (H-S), increased markedly. The impact of class II malocclusion on parents' U-MPM was greater than their children. Conclusion . The oropharyngeal space of upper airway becomes smaller and hyoid shifts downwards due to class II malocclusion. Class III malocclusion results in decreased nasopharyngeal gap with hyoid to shift upward. The influence of class II malocclusion on the upper pharyngeal tract of parents was greater than their children.